ANALISIS DAN PERANCANGAN SISTEM INFORMASI GEOGRAFIS PEMETAAN SEKOLAH DI KABUPATEN TANJUNG JABUNG BARAT - Pradana, Lazuardi Yudha; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
Research on the Education Office of Tanjung Jabung Barat District was motivated because schools inTanjung Jabung Barat District currently number 321 in 13 districts, with more and more existing schoolbuildings there are problems about how to find the position of the school, as well as problems in gettinginformation about facilities to support teaching and learning activities in the school and for the educationdepartment in determining the distribution of schools in an area (dense population but few schools. Thesystem development method used is Prototypr using modeling tools Use Case Diagrams, Activity Diagrams,and Class Diagrams. Software used by Google Maps, as well as the hardware used by Global PositioningSystem (GPS) .This research was conducted so that it is expected that users can easily find out the location ofthe nearest school in Tanjung Jabung Barat District.